MENINGKATKAN KEMAMPUAN GURU DALAM MENERAPKAN MODEL PEMBELAJARAN MELALUI KEGIATAN SUPERVISI KELAS - Tarmizi Tarmizi (PRODI PJKR UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2021)
ABSTRACT: This research is motivated by teachers who rarely use learning models in every learning process because of the teacher's lack of understanding of learning models that can make it easier for teachers to implement the learning process in the classroom. This research is classified as a school action research, with four main steps, namely: planning the action, implementing the action, observing (observation), and reflecting, involving nine teachers as a sample at SMP Negeri 01 Muara Bungo. The results of the study can be concluded that using learning models in the teaching and learning process can increase teacher motivation and student learning. This is evident in the first cycle of all teachers (nine people) including the assessment of learning outcomes in the lesson plans of implementing their learning models even though the sub-components (techniques, instrument forms, questions), scoring guidelines, and answer keys are incomplete. If percentage, 56%. each teacher gets a score of 1 and 3 (not good and good), three people get a score of 2 (good enough), and one person gets a score of 4 (very good). In the second cycle the nine teachers included the assessment of learning outcomes in the RPP for the application of the learning models even though there were teachers who were still wrong in determining the technique and form of the assessment. Seven people got a score of 3 (good) and one person got a score of 4 (very good). If in percentage, 78%, there is an increase of 22% from cycle I. Keywords: learning models, supervision, school principals